Toxoplasma gondii Mechanisms of Entry Into Host Cells - Juliana Portes; Juliana Portes; Emile Barrias; Renata Travassos; Renata Travassos; Márcia Attias; Márcia Attias; Wanderley de Souza; Wanderley de Souza (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasma gondii, the causative agent of toxoplasmosis, is an obligate intracellular protozoan parasite. Toxoplasma can invade and multiply inside any nucleated cell of a wide range of homeothermic hosts. The canonical process of internalization involves several steps: an initial recognition of the host cell surface and a sequential secretion of proteins from micronemes followed by rhoptries that assemble a macromolecular complex constituting a specialized and transient moving junction. The parasite is then internalized via an endocytic process with the establishment of a parasitophorous vacuole (PV), that does not fuse with lysosomes, where the parasites survive and multiply. This process of host cell invasion is usually referred to active penetration. Using different cell types and inhibitors of distinct endocytic pathways, we show that treatment of host cells with compounds that interfere with clathrin-mediated endocytosis (hypertonic sucrose medium, chlorpromazine hydrochloride, and pitstop 2 inhibited the internalization of tachyzoites). In addition, treatments that interfere with macropinocytosis, such as incubation with amiloride or IPA-3, increased parasite attachment to the host cell surface but significantly blocked parasite internalization. Immunofluorescence microscopy showed that markers of macropinocytosis, such as the Rab5 effector rabankyrin 5 and Pak1, are associated with parasite-containing cytoplasmic vacuoles. These results indicate that entrance of T. gondii into mammalian cells can take place both by the well-characterized interaction of parasite and host cell endocytic machinery and other processes, such as the clathrin-mediated endocytosis, and macropinocytosis.